PENGARUH KEMAMPUAN DAN MOTIVASI KERJA TERHADAP KUALITAS PELAYANAN PERAWAT PADA RSM AHMAD DAHLAN KEDIRI - Yudiarso, Agus Wahju (Jurnal al Hikmah, 2017)
Ability and motivation is something that can affect the quality of services provided nurses. Hospitals need to improve the ability and motivation of nurses to improve service to patients. The purpose of this study was to determine the influence of the ability and motivation of the nurses on the quality of nursing services at RSM Ahmad Dahlan. The method used in this research is quantitative descriptive with the number of respondents is all nurses a number of 60 people .. The results showed that the variables x1 and quality of service capabilities y have a relationship with the correlation value of 0.317, the motivation variable y x2 and service quality have a relationship with a correlation value of 0324. Variable partially ability and motivation does not affect the quality of the waiters proved with sig 0154 and 0:12 on the verge of 0.05 .. But variable ability and motivation of nurses affect the quality of nursing services by 13, 7%, while 86.3% nurse service quality is influenced by other variables not examined. From the end result can be obtained the following regression equation Y = 0206 + 0220 motivational abilities.